Cancer: a major cardiac comorbidity with implications on cardiovascular metabolism - Finke, Daniel; Heckmann, Markus B.; Frey, Norbert; Lehmann, Lorenz (Frontiers in physiology, 2021)
Cardiovascular diseases have multifactorial causes. Classical cardiovascular risk factors, such as arterial hypertension, smoking, hyperlipidemia and diabetes associate with the development of vascular stenoses and coronary heart disease. Further comorbidities and its impact on cardiovascular metabolism have gotten more attention recently. Thus, also cancer biology may affect the heart, apart from cardiotoxic side effects of chemotherapies. Cancer is a systemic disease which primarily leads to metabolic alterations within the tumor. An emerging number of preclinical and clinical studies focuses on the interaction between cancer and a maladaptive crosstalk to the heart. Cachexia and sarcopenia can have dramatic consequences for many organ functions, including cardiac wasting and heart failure. These complications significantly increase mortality and morbidity of heart failure and cancer patients. There are concurrent metabolic changes in fatty acid oxidation and glucose utilization in heart failure as well as in cancer, involving central molecular regulators, such as PGC-1. Further, specific inflammatory cytokines (IL-1, IL-6, TNF-, INF-), non-inflammatory cytokines (myostatin, SerpinA3, Ataxin-10) and circulating metabolites (D2-HG) may mediate a direct and maladaptive crosstalk of both diseases. Additionally, cancer therapies such as anthracyclines and angiogenesis inhibitors target common metabolic mechanisms in cardiomyocytes and malignant cells. This review focuses on cardiovascular, cancerous and cancer therapy-associated alterations on the systemic and cardiac metabolic state.
Gesehen am 15.12.2021